Q Fever Presenting as Recurrent, Culture-Negative Endocarditis with Aortic Prosthetic Valve Failure: A Case Report and Review of the Literature - Abeer N AlShukairi; Muhammad G Morshed; Neil E Reiner (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present report describes a case of recurrent, culture-negative endocarditis presenting with aortic prosthetic valve dysfunction in a 62-year-old man who required four valve replacement surgeries. On each occasion, he presented with valve failure. Fever was only documented during his first presentation. Furthermore, no vegetations were detectable on his aortic valve at transesophageal echocardiography. On the occasion of his most recent presentation, a detailed history of animal exposure -- including hunting and skinning deer, moose and other large animals with his bare hands -- was the only clue to his diagnosis. Serum antibodies against Coxiella burnetii were strongly positive, and C burnetii DNA was detected by polymerase chain reaction from his resected aortic valve tissue. Q fever is a worldwide zoonotic infection with diverse reservoirs. This diagnosis should be considered when evaluating unexplained prosthetic valve dysfunction, particularly in the setting of animal exposure.